Aerogel composite molding process with high tensile strength
Patent Information
- Application Number
- CN202611165300.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
其一,纤维增强体与气凝胶基体之间的界面结合强度不足,在受到拉伸载荷时,气凝胶基体易从纤维表面剥离,导致复合材料整体抗拉强度提升有限
(1)本发明通过三维编织技术构建具有X-Y-Z三向纤维网络结构的预制体,Z向增强纤维的引入有效提升了复合材料在厚度方向的抗拉性能,使复合材料能够抵抗多方向的拉伸载荷,显著提高了整体抗拉强度。
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerogel composite materials technology, specifically to a molding process for high tensile strength aerogel composite materials. Background Technology
[0002] Aerogels are novel materials with a nanoporous network structure. Due to their excellent properties such as low density, high specific surface area, and low thermal conductivity, they have shown great application potential in thermal insulation fields such as building insulation, thermal pipeline insulation, and aerospace. However, traditional silica aerogel materials have inherent defects such as low strength and high brittleness. Their tensile strength is far below the requirements of practical applications, which seriously limits their widespread application in structural load-bearing fields.
[0003] Currently, using fibers as reinforcement is an important way to improve the mechanical properties of aerogels. Existing technologies include using fiber mats, fiber cloths, or fiber meshes as reinforcing substrates, impregnating aerogel precursors into the fiber substrate via a sol-gel method, and then drying to obtain aerogel composite materials. However, existing fiber-reinforced aerogel composite materials still have the following shortcomings: First, the interfacial bonding strength between the fiber reinforcement and the aerogel matrix is insufficient. Under tensile loads, the aerogel matrix easily peels off from the fiber surface, resulting in limited improvement in the overall tensile strength of the composite material. Second, in traditional impregnation processes, the sol-gel penetration into the fiber preform is uneven, making it difficult to achieve sufficient filling of the aerogel within the fiber bundles and between fibers, resulting in numerous defects and stress concentration points within the composite material. Third, existing processes mostly use unidirectional fiber reinforcement, which is insufficient to effectively resist multidirectional tensile loads. Fourth, aerogel composites are prone to shrinkage cracking during the drying process, further deteriorating the material's mechanical properties.
[0004] Therefore, developing a molding process that can significantly improve the tensile strength of aerogel composites has important practical significance and application value. Summary of the Invention
[0005] The purpose of this invention is to provide a molding process for high tensile strength aerogel composite materials to solve the technical problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a molding process for a high tensile strength aerogel composite material, comprising step S1: preparation of a three-dimensional braided fiber preform: Using chopped fibers, continuous fibers, or fiber mats as the base material, a three-dimensional weaving technique is employed to weave the fibers into a three-dimensional network structure preform. The three-dimensional weaving can be any one of three-dimensional orthogonal weaving, three-dimensional four-directional weaving, or three-dimensional five-directional weaving. During the weaving process, reinforcing fibers are introduced into the thickness direction (Z-direction) of the fiber preform to form a three-dimensional integral structure in which the XY planar fiber network and Z-direction fiber bundles intertwine. The fibers are selected from one or more of glass fibers, quartz fibers, carbon fibers, aramid fibers, mullite fibers, and aluminosilicate fibers. The fiber volume fraction of the fiber preform is 5% to 30%.
[0007] Preferably, step S2 includes: interface modification treatment of the fiber surface. The three-dimensional braided fiber preform obtained in step S1 is immersed in a modification solution and treated at 30-80°C for 30-180 minutes to modify the fiber surface interface. The modification solution is any one of silane coupling agent solution, titanate coupling agent solution or dopamine solution, with a concentration of 0.5%-10%. After modification treatment, the fiber preform is taken out and dried at 60-120°C for 1-4 hours to obtain a surface-modified three-dimensional braided fiber preform.
[0008] Preferably, step S3 is included: preparation of the aerogel precursor sol. A silicon source precursor, solvent, acid catalyst, and water are mixed in a certain proportion and hydrolyzed at 20-60°C for 1-6 hours to obtain a hydrolysate. The silicon source precursor is one or more of tetraethyl orthosilicate, methyl orthosilicate, and methyltrimethoxysilane. The solvent is one or more of ethanol, isopropanol, or acetone. Then, an alkaline catalyst is added to the hydrolysate to adjust the pH to 7-9, and stirring is continued for 10-60 minutes to obtain an aerogel precursor sol.
[0009] Preferably, step S4 is included: gradient vacuum impregnation molding. The surface-modified three-dimensional braided fiber preform obtained in step S2 is placed in a vacuum impregnation tank and evacuated to a vacuum degree of -0.08 to -0.1 MPa for 10 to 30 minutes. Then, the aerogel precursor sol obtained in step S3 is injected into the impregnation tank at a flow rate of 0.5 to 5 mL / min. After the sol completely impregnates the fiber preform, the vacuum is removed and the pressure is maintained at a positive pressure of 0.2 to 1.0 MPa for 10 to 60 minutes. The above vacuum-pressure impregnation cycle is repeated 2 to 5 times to ensure that the aerogel precursor sol fully fills the fiber bundles and inter-fiber pores of the three-dimensional braided fiber preform.
[0010] Preferably, step S5 is included: sol-gel and aging. The fiber preform impregnated in step S4 is taken out along with the mold and allowed to stand at 20~40℃ for 4~24 hours to gel, thus obtaining a fiber-reinforced aerogel wet gel composite material; then the wet gel composite material is immersed in an aging solution and aged at 40~80℃ for 6~48 hours; the aging solution is any one of ethanol, isopropanol or tetraethyl orthosilicate / ethanol mixed solution.
[0011] Preferably, step S6 is included: gradient solvent replacement. The aged wet gel composite material from step S5 is sequentially immersed in a displacement solution with a concentration gradient for solvent replacement. The displacement solution is an ethanol / n-hexane mixture or an ethanol / acetone mixture. The concentration gradient of the displacement solution is: ethanol volume fraction 100%→75%→50%→25%→0%, and the replacement time is 2~6 hours for each concentration gradient.
[0012] Preferably, step S7 is included: co-drying. The composite material after solvent replacement in step S6 is subjected to synergistic drying, which involves first supercritical drying or atmospheric pressure drying, followed by hot pressing for shaping. Sub-step S7-1: The solvent-displaced composite material is placed in a drying device for supercritical drying or atmospheric pressure drying; the supercritical drying uses carbon dioxide as the drying medium, the drying temperature is 35~60℃, and the pressure is 8~12MPa; the atmospheric pressure drying is carried out at 50~150℃ for 6~24 hours. Sub-step S7-2: The composite material dried in sub-step S7-1 is placed in a hot press and hot-pressed for 10-60 minutes at 80-200℃ and 5-30MPa to obtain a high tensile strength aerogel composite material.
[0013] Preferably, step S8 is included: surface enhancement treatment. The surface of the aerogel composite material obtained in step S7 is coated or impregnated with a reinforcing coating solution, wherein the reinforcing coating solution is any one of a polyimide precursor solution, an epoxy resin solution, or a silicone resin solution, and the coating thickness is 0.01~0.5mm; after coating, it is cured at 80~250℃ for 1~6 hours to obtain a surface-reinforced aerogel composite material.
[0014] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention constructs a preform with an XYZ three-dimensional fiber network structure through three-dimensional weaving technology. The introduction of Z-direction reinforcing fibers effectively improves the tensile properties of the composite material in the thickness direction, enabling the composite material to resist tensile loads in multiple directions and significantly improving the overall tensile strength.
[0015] (2) By performing interface modification treatment on the fiber surface, the present invention effectively improves the interfacial bonding strength between the fiber and the aerogel matrix, so that the aerogel can be firmly anchored on the fiber surface and the load can be effectively transferred from the aerogel matrix to the fiber reinforcement when subjected to tensile load, thus avoiding interfacial peeling failure.
[0016] (3) The present invention adopts a vacuum-pressure cyclic gradient impregnation process. Through repeated vacuum degassing and pressure penetration, the aerogel precursor sol can fully penetrate into the micropores inside the fiber bundle, realizing the uniform and full filling of aerogel in the fiber preform, and greatly reducing the defects and stress concentration points inside the composite material.
[0017] (4) The present invention adopts a synergistic drying process combining gradient solvent replacement with supercritical / normal pressure drying and hot pressing. Gradient replacement effectively reduces capillary stress during the drying process, and hot pressing further improves the density of the composite material and the bonding tightness of the fiber-aerogel interface, effectively suppressing drying cracking.
[0018] (5) The present invention forms a dense reinforcing layer on the surface of the composite material through surface reinforcement treatment, which further improves the surface tensile strength and overall mechanical properties of the composite material. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1 This embodiment provides a molding process for aerogel composite material with high tensile strength. The specific steps are as follows: (1) Using aluminum silicate fiber as the substrate, a three-dimensional woven fiber preform with a fiber volume fraction of 15% is prepared by three-dimensional four-way weaving technology. (2) The fiber preform is immersed in a 3% γ-aminopropyltriethoxysilane (KH-550) ethanol solution and treated at 60°C for 120 minutes. After removal, it is dried at 80°C for 2 hours to obtain a surface-modified three-dimensional woven fiber preform. (3) Tetraethyl orthosilicate, ethanol, water and hydrochloric acid are mixed in a molar ratio of 1:4:2:0.01 and hydrolyzed at 40°C for 4 hours to obtain a hydrolysate. Then, ammonia is added to the hydrolysate to adjust the pH to 8, and stirring is continued for 30 minutes to obtain an aerogel precursor sol. (4) Place the surface-modified three-dimensional braided fiber preform in a vacuum impregnation tank, evacuate to -0.095 MPa, and maintain for 20 minutes; inject sol at a flow rate of 2 mL / min, and after the sol completely impregnates the preform, remove the vacuum and maintain pressure at 0.5 MPa for 30 minutes; repeat the above cycle 3 times. (5) Let the impregnated preform stand at 30°C for 12 hours to gel, and then immerse it in ethanol and age it at 60°C for 24 hours. (6) Immerse the aged wet gel composite material in ethanol / n-hexane mixed solutions with volume fractions of 100%, 75%, 50%, 25%, and 0% in sequence, and replace it for 4 hours at each concentration gradient. (7) Place the solvent-replaced composite material in a supercritical drying kettle, use CO2 as the medium, and dry it at 45°C and 10 MPa for 6 hours; then place the dried composite material in a hot press and hot press it at 120°C and 15 MPa for 30 minutes to set it. (8) The hot-pressed composite material was immersed in a 10% polyimide precursor solution for coating, then removed and cured at 150°C for 3 hours to obtain the final product. The density of the aerogel composite material prepared in this embodiment was tested to be 0.22 g / cm³. 3 It has a thermal conductivity of 0.021 W / (m·K) and a tensile strength of 28.6 MPa.
[0021] Example 2 The difference between this embodiment and Embodiment 1 is as follows: in step (1), quartz fiber is used as the substrate, with a fiber volume fraction of 20%; in step (2), the modification solution is a dopamine solution (concentration of 2 mg / mL), the treatment temperature is 40℃, and the treatment time is 180 minutes; in step (7), atmospheric pressure drying is used, drying at 80℃ for 12 hours, and hot pressing is performed at 150℃, pressure of 20 MPa, and time of 20 minutes. The remaining steps are the same as in Embodiment 1. The density of the aerogel composite material prepared in this embodiment is 0.28 g / cm³. 3 It has a thermal conductivity of 0.023 W / (m·K) and a tensile strength of 32.1 MPa.
[0022] Example 3 The difference between this embodiment and Embodiment 1 is as follows: In step (1), a mixture of carbon fiber and glass fiber (mass ratio 1:1) is used as the substrate, and a three-dimensional orthogonal weaving technique is employed, with a fiber volume fraction of 10%; in step (3), the silicon source precursor is a mixture of methyl orthosilicate and methyltrimethoxysilane (molar ratio 1:1); in step (4), the vacuum degree is -0.08 MPa, the positive pressure is 0.8 MPa, and the number of cycles is 5; in step (7), the hot pressing setting temperature is 180℃, the pressure is 10 MPa, and the time is 45 minutes. The remaining steps are the same as in Embodiment 1. The density of the aerogel composite material prepared in this embodiment is 0.25 g / cm³. 3 It has a thermal conductivity of 0.024 W / (m·K) and a tensile strength of 25.3 MPa.
[0023] Comparative Example 1 The difference between this comparative example and Example 1 is that the fiber surface interface modification treatment in step (2) is omitted, and the unmodified fiber preform is directly used in subsequent steps. The remaining steps are the same as in Example 1. Testing showed that the tensile strength of the aerogel composite material prepared in Comparative Example 1 was 12.4 MPa, significantly lower than the 28.6 MPa in Example 1, indicating that the fiber surface interface modification treatment plays an important role in improving tensile strength.
[0024] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (4), atmospheric pressure impregnation (without applying vacuum and positive pressure) is used instead of gradient vacuum impregnation. The remaining steps are the same as in Example 1.
[0025] The tensile strength of the aerogel composite material prepared in Comparative Example 2 was 15.8 MPa, which was lower than that of Example 1 (28.6 MPa). This indicates that the gradient vacuum impregnation process can effectively improve the uniformity of aerogel filling in the fiber preform, thereby increasing the tensile strength.
[0026] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A molding process for a high tensile strength aerogel composite material, characterized in that: Including step S1: Preparation of the three-dimensional braided fiber preform: Using chopped fibers, continuous fibers, or fiber mats as the base material, a three-dimensional weaving technique is employed to weave the fibers into a three-dimensional network structure preform. The three-dimensional weaving can be any one of three-dimensional orthogonal weaving, three-dimensional four-directional weaving, or three-dimensional five-directional weaving. During the weaving process, reinforcing fibers are introduced into the thickness direction (Z-direction) of the fiber preform to form a three-dimensional integral structure in which the XY planar fiber network and Z-direction fiber bundles intertwine. The fibers are selected from one or more of glass fibers, quartz fibers, carbon fibers, aramid fibers, mullite fibers, and aluminosilicate fibers. The fiber volume fraction of the fiber preform is 5% to 30%.
2. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S2: interfacial modification treatment of the fiber surface: The three-dimensional braided fiber preform obtained in step S1 is immersed in the modification solution and treated at 30~80℃ for 30~180 minutes to perform interface modification on the fiber surface. The modified solution is any one of a silane coupling agent solution, a titanate coupling agent solution, or a dopamine solution, with a concentration of 0.5% to 10%. After modification, the fiber preform is taken out and dried at 60~120℃ for 1~4 hours to obtain a surface-modified three-dimensional woven fiber preform.
3. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S3: Preparation of aerogel precursor sol: A silicon source precursor, solvent, acid catalyst, and water are mixed in a certain proportion and hydrolyzed at 20-60°C for 1-6 hours to obtain a hydrolysate. The silicon source precursor is one or more of tetraethyl orthosilicate, methyl orthosilicate, and methyltrimethoxysilane. The solvent is one or more of ethanol, isopropanol, or acetone. Then, an alkaline catalyst is added to the hydrolysate to adjust the pH to 7-9, and stirring is continued for 10-60 minutes to obtain an aerogel precursor sol.
4. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S4: gradient vacuum impregnation molding: The surface-modified three-dimensional braided fiber preform obtained in step S2 is placed in a vacuum impregnation tank and evacuated to a vacuum degree of -0.08 to -0.1 MPa for 10 to 30 minutes. Then, the aerogel precursor sol obtained in step S3 is injected into the impregnation tank at a flow rate of 0.5 to 5 mL / min. After the sol completely impregnates the fiber preform, the vacuum is removed and the pressure is maintained at a positive pressure of 0.2 to 1.0 MPa for 10 to 60 minutes. The above vacuum-pressure impregnation cycle is repeated 2 to 5 times to ensure that the aerogel precursor sol fully fills the fiber bundles and inter-fiber pores of the three-dimensional braided fiber preform.
5. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S5: Sol-Gel and Aging: Take out the fiber preform impregnated in step S4 along with the mold, and let it stand at 20~40℃ for 4~24 hours to gel, and obtain fiber reinforced aerogel wet gel composite material. The wet gel composite material is then immersed in an aging solution and aged at 40-80°C for 6-48 hours; the aging solution is any one of ethanol, isopropanol, or a mixture of tetraethyl orthosilicate and ethanol.
6. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S6: gradient solvent replacement: The aged wet gel composite material from step S5 is sequentially immersed in a displacement solution with a concentration gradient for solvent replacement. The displacement solution is an ethanol / n-hexane mixture or an ethanol / acetone mixture. The concentration gradient of the displacement solution is: ethanol volume fraction 100%→75%→50%→25%→0%, and the replacement time is 2~6 hours for each concentration gradient.
7. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S7: Co-drying: The composite material after solvent replacement in step S6 is subjected to synergistic drying, which involves first supercritical drying or atmospheric pressure drying, followed by hot pressing for shaping. Sub-step S7-1: The solvent-displaced composite material is placed in a drying device for supercritical drying or atmospheric pressure drying; the supercritical drying uses carbon dioxide as the drying medium, the drying temperature is 35~60℃, and the pressure is 8~12MPa; the atmospheric pressure drying is carried out at 50~150℃ for 6~24 hours. Sub-step S7-2: The composite material dried in sub-step S7-1 is placed in a hot press and hot-pressed for 10-60 minutes at 80-200℃ and 5-30MPa to obtain a high tensile strength aerogel composite material.
8. The molding process for a high tensile strength aerogel composite material according to claim 1, characterized in that: Including step S8: Surface enhancement treatment: The surface of the aerogel composite material obtained in step S7 is coated or impregnated with a reinforcing coating solution, wherein the reinforcing coating solution is any one of a polyimide precursor solution, an epoxy resin solution, or a silicone resin solution, and the coating thickness is 0.01~0.5 mm. After coating, the aerogel composite material is cured at 80~250℃ for 1~6 hours to obtain a surface-reinforced aerogel composite material.